Pelatihan Pengelolaan Manik-Manik Mutiara menjadi Kerajinan Tangan Kreatif Berupa Bunga Hias pada Masyarakat Kelurahan Kessilampe Kec. Kendari Kab. Kendari - Rizal Rizal; Abdullah Igo, BD; Muh. Ilham; Hasnawati Hasnawati; Murni Nia; Nurvianti Nurvianti; Harjun Harjun (Indonesia Berdampak: Jurnal Pengabdian kepada Masyarakat, 2026)
This research aims to introduce the public to the uses of pearl beads, as well as utilizing pearl beads to make crafts. The problem focused on this research is how students and the community can take advantage of business opportunities, as well as how to provide students and the community with knowledge about business management, starting a business, and how to market products. The implementation method used in this training is the lecture and practice method. The result of the implementation of the activities that we carried out was a creative handicraft product in the form of a flower from pearl beads named PEARL FLOWER. This product is a creativity and expertise in making handicrafts such as flowers from pearl beads to produce unique and attractive works of art. Flowers from pearl beads are one form of handicraft that is popular and sought after by many people. This product adds a beautiful and elegant touch to home decor or special events. Making flowers from pearl beads involves selecting colors, arranging beads, and installation techniques, this requires good manual skills and precision. Handicrafts such as flowers from pearl beads can be a fun and satisfying hobby. The process of making them can provide artistic satisfaction and hone creative skills and can be a profitable business opportunity. Thus, creative handicrafts such as flowers made from pearl beads have high artistic value and business potential, in addition, they can provide pleasure and satisfaction to the maker and become an attractive decoration in various contexts.